Analisis Tingkat Kejenuhan Siswa Sebelum, Selama, dan Setelah Pembelajaran Sains - Amel Fadillah; Ogi Danika Pranata; Lia Angela (UNIB Press, 2024)
This research aimed to reveal and compare students' levels of boredom before, during, and after science learning, utilizing a quantitative approach with descriptive and comparative methods. The study included a sample of 188 students from MTsN 1 Sungai Penuh City, selected through purposive sampling. Data on student boredom during science learning were collected using the Academic Emotions Questionnaire: Class Related. This questionnaire comprises 80 statements, with 23 for before, 43 for during, and 14 for after participating in science learning. Each statement offers five alternative responses, ranging from strongly agree to strongly disagree. Subsequently, the collected data were analyzed using descriptive statistics and analysis of variance (ANOVA). The research findings indicate that students' overall boredom in science learning falls within the medium category—before (2.14), during learning (2.55), and after science learning (2.40). ANOVA testing revealed a significant difference in boredom levels before, during, and after science learning. Notably, the highest saturation occurred during learning, followed by after and before learning. These results emphasize the need for teachers to consider discussions for each learning condition and factors contributing to student boredom when designing learning experiences. The ultimate goal is to minimize the level of boredom in science learning.